Analysis Of The Relationship Between Pharmacists' Knowledge, Attitude, And Perception Levels Towards Telepharmy Implementation In Sukoharjo Regency - Fiska Febriani Fikri; Kharisma Jayak Pratama; Hidayah Apriliawan (CV. AFDIFAL MAJU BERKAH, 2026)
The Covid-19 pandemic has accelerated the adoption of technology in healthcare services, including the implementation of telepharmacy. The success of telepharmacy implementation depends on the readiness of pharmacists in terms of their knowledge, attitudes, and perceptions. This study aims to analyze the relationship between the level of knowledge, attitudes, and perceptions of pharmacists towards the implementation of telepharmacy in the Sukoharjo Regency. This study is a qualitative descriptive study with a cross-sectional approach. The study sample consisted of 30 pharmacists working in pharmacies and community health centers in Sukoharjo Regency, selected using purposive sampling. Data were collected using a questionnaire that had been tested for validity and reliability, as well as in-depth interviews. Data analysis included univariate and bivariate analysis with chi-square. The results showed that the majority of pharmacists had a good level of knowledge (mean 76.7%), indicating that pharmacists had a good understanding. Pharmacists' attitudes were in the adequate category (mean 60%), and pharmacists' perceptions were in the adequate category (mean 70%). Statistical analysis using chi-square indicated that there was a significant relationship between pharmacists' knowledge and perceptions, with a p-value of 0.014 (p <0.05). There was a significant relationship between the variables of attitude and perception, as indicated by a p-value of 0.001 (p <0.05). The conclusion of the implementation of tele-pharmacy is not only in terms of knowledge, but also in strengthening positive attitudes through supportive infrastructure, technical training, and clear regulations.